Quantitative collagen assessment in right ventricular myectomies from patients with tetralogy of Fallot. (6th January 2021) - Wülfers, Eike M; Greiner, Joachim; Giese, Max; Madl, Josef; Kroll, Johannes; Stiller, Brigitte; Kohl, Peter; Rog-Zielinska, Eva A; Fürniss, Hannah E
Abstract: Aims: Patients with tetralogy of Fallot (TOF) are often affected by right ventricular fibrosis, which has been associated with arrhythmias. This study aimed to assess fibrosis distribution in right ventricular outflow tract (RVOT) myocardium of TOF patients to evaluate the utility of single histology-section analyses, and to explore the possibility of fibrosis quantification in unlabelled tissue by second harmonic generation imaging (SHGI) as an alternative to conventional histology-based assays. Methods and results: We quantified fibrosis in 11 TOF RVOT samples, using a tailor-made automated image analysis method on Picrosirius red-stained sections. In a subset of samples, histology- and SHGI-based fibrosis quantification approaches were compared. Fibrosis distribution was highly heterogeneous, with significant and comparable variability between and within samples. We found that, on average, 67.8 mm 2 of 10 µm thick, histologically processed tissue per patient had to be analysed for accurate fibrosis quantification. SHGI provided data faster and on live tissue, additionally enabling quantification of collagen anisotropy. Conclusion: Given the high intra-individual heterogeneity, fibrosis quantification should not be conducted on single sections of TOF RVOT myectomies. We provide an analysis algorithm for fibrosis quantification in histological images, which enables the required extended volume analyses in these patients.